Guidelines for time-to-event end-point definitions in adjuvant randomised trials for patients with localised colon cancer: Results of the DATECAN initiative. (May 2020) - Cohen, Romain; Vernerey, Dewi; Bellera, Carine; Meurisse, Aurélia; Henriques, Julie; Paoletti, Xavier; Rousseau, Benoît; Alberts, Steven; Aparicio, Thomas; Boukovinas, Ioannis; Gill, Sharlene; Goldberg, Richard M.; et al.
Abstract: Background: The variability of definitions for time-to-event (TTE) end-points impacts the conclusions of randomised clinical trials (RCTs). The Definition for the Assessment of Time-to-event Endpoints in CANcer (DATECAN) initiative aims to provide consensus definitions for TTE end-points used in RCTs. Here, we formulate guidelines for adjuvant colon cancer RCTs. Methods: We performed a literature review to identify TTE end-points and events included in their definition in RCT publications. Then, a consensus was reached among a panel of international experts, using a formal modified Delphi method, with 2 rounds of questionnaires and an in-person meeting. Results: Twenty-four experts scored 72 events involved in 6 TTE end-points. Consensus was reached for 24%, 57% and 100% events after the first round, second round and in-person meeting. For RCTs not using overall survival as their primary end-point, the experts recommend using disease-free survival (DFS) rather than recurrence-free survival (RFS) or time to recurrence (TTR) as the primary end-point. The consensus definition of DFS includes all causes of death, second primary colorectal cancers (CRCs), anastomotic relapse and metastatic relapse as an event, but not second primary non-CRCs. Events included in the RFS definition are the same as for DFS with the exception of second primary CRCs. The consensus definition of TTR includes anastomotic or metastatic relapse, death with evidence of recurrence and death from CC cause. Conclusion: Standardised definitions of TTE end-points ensure the reproducibility of the end-points between RCTs and facilitate cross-trial comparisons. These definitions should be integrated in standard practice for the design, reporting and interpretation of adjuvant CC RCTs. Highlights: Randomised trials for adjuvant therapy in colon cancer (CC) use multiple time-to-event (TTE) end-points that lack standardised definitions. Recommendations for the definition of TTE end-point in adjuvant CC randomised trials were established. These guidelines should become standard practice because they would facilitate data interpretation and across-trial comparisons.